2008
DOI: 10.1177/1321103x08089888
|View full text |Cite
|
Sign up to set email alerts
|

When minorities are the majority: voices from a teacher/researcher project in a multicultural school in Sweden

Abstract: A B S T R AC T What can a music teacher do, when confronted with 99 percent immigrant students? How does he or she interpret guidelines in national governing documents and, at the same time, listen to the needs of the students? This article opens the doors to two music classrooms in Malmö, a Swedish town with 27 percent of the population born abroad. The project 'Social Inclusion in Music education'(SIM), described here, sought to give voice to both teachers and students who work and live in multicultural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 3 publications
1
37
0
2
Order By: Relevance
“…Also, as Harris (2006) points out, for some students with Muslim backgrounds the music education they meet in Western classrooms may seem to them to be incompatible with their religious beliefs. However, neither of these issues seemed to dominate the multicultural school in which Saether (2008) conducted her research on social inclusion in music education. She found that very few of the immigrant students reported to listen to music from their own culture, a phenomenon she interpreted as a wish to be 'freed from cultural identity ' (2008, 33), or rather to be freed from the societal demand that one ought to 'present a [particular] cultural identity ' (2008, 33).…”
Section: Immigrant Students' Experiences Of Music and Music Educationmentioning
confidence: 94%
See 2 more Smart Citations
“…Also, as Harris (2006) points out, for some students with Muslim backgrounds the music education they meet in Western classrooms may seem to them to be incompatible with their religious beliefs. However, neither of these issues seemed to dominate the multicultural school in which Saether (2008) conducted her research on social inclusion in music education. She found that very few of the immigrant students reported to listen to music from their own culture, a phenomenon she interpreted as a wish to be 'freed from cultural identity ' (2008, 33), or rather to be freed from the societal demand that one ought to 'present a [particular] cultural identity ' (2008, 33).…”
Section: Immigrant Students' Experiences Of Music and Music Educationmentioning
confidence: 94%
“…For example, while many of the Helsinki students (who in the year of the investigation had less time for playing together than the other student interviewees) emphasised that a good class spirit as well as listening carefully to the teacher were prerequisites for musical cooperation, several of the other interviewees understood class spirit and cohesion to be the result of such interactions (ref. Saether 2008). Furthermore, they pointed out that, in order for successful, musicrelated cooperation and interaction to occur, the participants would need to know how to give and take in a social situation, take responsibility for one's own actions, act as a leader, have one's ears 'open' (musically speaking), be able to negotiate as well as know how to be organised and be willing to listen to the others: The majority gets to decide.…”
Section: The Process Of Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Studies of children's intercultural transmission of music within a social framework, the role of music in the creation of transitional identities for immigrant and bicultural children, and children's uses of mediated music within these processes also represent an emerging field of interest (Campbell and Wiggins 2013;Green 2011;Karlsen 2013;Lum 2008;Marsh 2008Marsh , 2012Marsh , 2013Minks 2006Minks , 2013Saether 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Forskning på krysskulturell musikkopplaering og musikalsk utøving har en lang historie der sentrale aktører har diskutert hvordan mangfoldet av verdensmusikk skal anerkjennes og implementeres i musikklasserommet (Campbell, et al, 2005;Elliott, 2013;Schippers, 2010;Volk, 1998). Min studie (Strøm, 2016) inngår i en rekke av nyere studier på krysskulturell musikkopplaering og musikalske praksiser med et erfaringsbasert fokus, som vektlegger betydningen av at unge mennesker får definere og integrere sin «egen» musikk (Saether, 2008(Saether, , 2010Nethsinghe, 2012;Cain, 2015;Heimonen & Westvall 2015;Karlsen & Westerlund, 2015;Westerlund, Partti & Karlsen, 2016;Karlsen, 2017;Kvaal, 2018).…”
Section: Forskning På Musikalsk Aktørskap Og Krysskulturell Musikkoppunclassified